Women's journalists in the practice of mass media in Semarang city - Lusi Setyo Wulandari; Nova Permata Sari (Universitas Negeri Yogyakarta, 2019)
This study aims to determine the balance between female and male journalists in the mass media, and the subjective experience of women journalists in carrying out their duties. Data collection was carried out by in-depth interviews and interviewees in this study as many as five people from print and electronic media, to determine the sources of researchers using purposive sampling. This research uses the descriptive qualitative method with gender structuration theory which is a combination of structuration theory and feminist analysis. The results of this study indicate that male dominance is still very strong in the mass media, this can be seen in terms of the number of female journalists in each company. In terms of wages, almost all have not received the same wages as male journalists and there is still violence received by women journalists in carrying out their duties. Violence received in the form of verbal and nonverbal violence and women journalists consider the violence that occurs is a risk of work. It is hoped that with this research companies, journalists and the public will become more aware of gender equality. The formation of a special organization for women journalists was also felt to be very important in solving the problems of women journalists.Penelitian ini bertujuan untuk mengetahui keseimbangan antara jurnalis perempuan dan laki laki di media massa, dan pengalaman subyektif jurnalis perempuan dalam menjalankan tugasnya. Pengambilan data dilakukan dengan wawancara mendalam dan narasumber dalam penelitian ini sebanyak lima orang dari media cetak dan media elektronik, untuk menentukan narasumber peneliti menggunakan proposive sampling. Penelitian ini menggunakan metode kualitatif deskriptif dengan teori strukturasi gender yang merupakan perpaduan antara teori strukturasi dan analisis feminis. Hasil dari penelitian ini menunjukkan bahwa dominasi laki-laki masih sangat kuat dalam media massa hal ini terlihat dari segi jumlah jurnalis perempuan yang ada dalam setiap perusahaan. Dari segi pengupahan, hampir semua belum mendapatkan upah yang sama dengan jurnalis laki-laki serta masih adanya kekerasan yang diterima para jurnalis perempuan dalam melakukan tugasnya. Kekerasan yang diterima berupa kekerasan verbal dan nonverbal dan para jurnalis perempuan menganggap kekerasan yang terjadi merupakan resiko dari pekerjaan. Diharapkan dengan adanya penelitian ini perusahan, jurnalis dan masyarakat semakin sadar akan kesetaraan gender. Pembentukan organisasi khusus jurnalis perempuan juga dirasa sangat penting dalam menyelesaikan permasalahan jurnalis perempuan.